An Inventory Model for Deteriorating Items with Two-Warehouse & Stock Dependent Demand using Genetic algorithm - Neha Chauhan, Ajay Singh Yadav (International Journal of Advanced Science and Technology, 2020)
A deterministic inventory model has been developed for the deterioration of items, whose demand depends on stocks with inflation effects with double storage facilities. The own warehouse (OW) has a fixed capacity of W units; the rented warehouse (RW) has unlimited capacity using Genetic algorithm. Here we assume that the cost of holding shares in RW is higher than that of OW. The shortage of stocks is permissible and partially overdue, and it is believed that stocks will deteriorate over time with a variable impairment rate using Genetic algorithm. The inflation effect was also taken into account for various costs associated with the inventory system using Genetic algorithm. A numerical example is also used to examine the behavior of the model using Genetic algorithm. The cost minimization technique is used to obtain expressions of total costs and other parameters using Genetic algorithm.